Single‐Material OECT‐Based Flexible Complementary Circuits Featuring Polyaniline in Both Conducting Channels. (16th October 2020) - Travaglini, Lorenzo; Micolich, Adam P.; Cazorla, Claudio; Zeglio, Erica; Lauto, Antonio; Mawad, Damia
Abstract: The organic electrochemical transistor (OECT) with a conjugated polymer as the active material is the elementary unit of organic bioelectronic devices. Improved functionalities, such as low power consumption, can be achieved by building complementary circuits featuring two or more OECTs. Complementary circuits commonly combine both p ‐ and n ‐type transistors to reduce power draw. While p ‐type OECTs are readily available, n ‐type OECTs are less common mainly due to poor stability of the n ‐type active channel material in aqueous electrolyte. Here, a complementary circuit is made using a pair of OECTs having polyaniline (PANI) as the channel material in both transistors. PANI, with a finite electrochemical window accessible at voltages lower than 1 V, exhibits a peak in current versus gate voltage when used as an active channel in an OECT. The current peak has two slopes, one n ‐like and one p ‐like, which correspond to different electrochemical regimes of the same underlying conjugated polymer. The electrochemistry enables the design of a complementary circuit using only PANI as the channel material. The PANI‐based circuit is shown to have excellent performance with gain of ≈7 and is transferred on a flexible biocompatible chitosan substrate with demonstrated operation in aqueous electrolyte. Abstract : A flexible electrochemically driven complementary circuit is made using a pair of identical organic electrochemical transistors (OECTs) featuring the same active channel based on the conjugated polymer, polyaniline. Polyaniline exhibits a peak in current versus gate voltage when used as an active channel in an OECT. This proof‐of‐concept study exploits this feature for the design of an inverter with unique characteristics.